Performance monitoring of EBUS for the staging and diagnosis of lung cancer: auditing the Greater Manchester EBUS service against new national standards. Issue 1 (25th June 2021) - Punjabi, Anshu; Al-Najjar, Haider; Teng, Benjamin; Borrill, Zoe; Brown, Louise; Nagarajan, Thapas; Gallagher, Joanna; Grundy, Seamus; Sundar, Ram; Higgins, Coral; Shackley, David; Sinnott, Nicola; et al.
Abstract : Introduction: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a pivotal test in lung cancer staging and diagnosis, mandating robust audit and performance monitoring of EBUS services. We present the first regional cancer alliance EBUS performance audit against the new National EBUS specification. Methods: Across the five EBUS centres in the Greater Manchester Cancer Alliance, data are recorded at the point of procedure, when pathological results are available and at 6 months postprocedure to review any further pathological sampling (eg, at surgical resection) and the outcome of clinical–radiological follow-up. Outcomes across all five centres were compared with national standards for all lung cancer EBUS procedures from 01 January 2017 to 31 December 2018. Results: 1899 lung cancer staging or diagnostic EBUS procedures were performed across the five centres during the study period; 1309 staging EBUS procedures and 590 diagnostic EBUS procedures. Major complications were seen in six cases (<1%). All five trusts demonstrated performance above that set national standards in key metrics for both staging and diagnostic EBUS, however the provision of adequate tissue for predictive marker testing was below national standards at one trust. Across Greater Manchester, 72% and 64% of patients had their EBUS procedure performed within 7 days of referral in 2017 and 2018, respectively. Only one out of five trusts met the national targets of >85% of procedures performed within 7 days of referral. Conclusion: The National EBUS service specification is an important framework to drive the quality of EBUS services across the UK. Our data provide assurance of appropriate performance and safety while also highlighting specific areas for attention that can be addressed with the support of the cancer alliance.